Effect of cyclodextrin glucosyltransferase extracted from Bacillus xiaoxiensis on wheat dough and bread properties - Lianzhan Yang; Jinxin Cai; Haifeng Qian; Yan Li; Hui Zhang; Xiguang Qi; Li Wang; Guoliang Cao (Frontiers in Nutrition, 2022)
In this study, the cyclodextrin glucosyltransferase (CGTase) was extracted from Bacillus xiaoxiensis. CGTase had negative effects on dough viscoelastic properties and gluten strength but had positive effects on bread baking qualities and anti-staling properties. Adding an appropriate amount of CGTase (less than 0.3 U/g) could improve the specific volume, crumb texture, crust color, moisture content, and crumb hardness of bread. The bread crumb with 0.4 U/g CGTase (based on flour weight) had the lowest retrogradation enthalpy of 0.53 ± 0.10 J/g and the lowest relative crystallinity of 16.1%, which indicated the alleviating effect of amylopectin crystallization. Moreover, CGTase reduced the moisture from forming crystal lattices and limited starch molecule migration. The T2 transverse relaxation results showed that the increase of immobilized water content in the bread with CGTase was lower than the control after 5 days of storage, which implied the water-holding capacity of the bread was enhanced and provided information on the inhibition of water migration. Hence, the CGTase could be a potential bread improver.